O silêncio invalidante por questão de vizinhança na compra e venda - Sousa, Alexandre Castro (2017)
The main goal of the present study is to analyze the possibility of invalidation of a seller's sale agreement due to the seller's omission regarding the neighborhood in which the property is located and to what extent a harmful interference prior to the sale of the property would force the seller to inform the buyer about a particular situation in the neighborhood. The main question is whether the buyer would have the right to know the circumstances surrounding the neighborhood of the property to be purchased. In this way, we will try to give the reader enough information to answer such questions, always using the principle of straightforward good faith as the main guideline, which will govern, above all, the criteria given by the doctrine to identify whether or not they should inform the other contractor so that it is possible to characterize the intentional silence and, consequently, to consider the cancellation of the legal transaction by omission